Digitalisation of business ecosystems in the modern economic paradigm in the context of digital transformation of the economy (Economics and region, 2025)
Digital business ecosystems are of particular importance from a practical point of view, as companies from various sectors of the economy seek to use external resources to meet the growing needs of customers. In today's business environment, the concept of digitalization of society and the economy is seen as the basis for introducing innovative changes. In this sense, digital transformation is aimed at diffusing digital technologies into all types of business and social life, which requires the creation of an appropriate regulatory environment. Digitalization is a major driver of global economic growth and a key factor in the development of the digital economy in Ukraine. An analysis of government initiatives to develop the digitalization of the national society and economy shows that this process is increasing in intensity in Ukraine. The digital transformation of business in Ukraine makes a significant contribution to sustainable economic growth, increasing the competitiveness of basic industries and innovative sectors of the economy. The use of digital technologies is becoming mandatory for many types of business in Ukraine operating in the modern competitive environment. In the context of Ukraine's European integration, there is a need to join European programmers of digitalization and digital transformation of business.
Keywords: business; ecosystem; digitalization; European integration of Ukraine; paradigm; digital transformation; digital technologies